Rural architecture and landscape gardening - Hazen, Leslie Eugene (My University, 1906)
Introduction: This treatise is divided into two parts, the first an illustrated composition on farm building construction including specifications, the second a manual of landscape gardening especially adapted to country homes. The attempt will be made to show what can be done, not simply what should be done, in other words this study is supposed to deal with practicalities, not ideals. For the sake of brevity no statement will be qualified more than absolutely necessary. Kansas conditions only are considered. The proper selection of a building site is made in reference to three important considerations, distance to public road, a good water supply, and natural drainage. Build near the public road for three reasons; first, passers-by break the sense of isolation so keenly felt by many country housewives; second, Uncle Sam's mail delivery is more service and enjoyment; and third, the home yard beautifies the view from the road and the market is a little closer. It is expensive to pipe water long distances so if other conditions are equal the location near water should be chosen although not desirable from a landscape gardener's point of view. Never build on low land or near a creek bottom if any other place can be procured. It is less expensive to pipe water to the top of a six hundred foot slope than pay the doctor bills caused by fevers. Gasses formed by decaying vegetable and animal matter settle in low places among hills on quiet nights making such places unfit to sleep in. Upland is also desirable because it furnishes drainage; water does not stand long on a rounding knoll or hilltop, and liquid filth is more quickly drained away so as not to create unsanitary conditions. The buildings necessary for a general farm of from eighty to three hundred and twenty acres are, a horse barn, cow barn, cattle shed, sheep and swine sheds, poultry houses, shop and dwelling. One building may serve several purposes but it is best to have buildings adapted especially to tile animals housed in them and avoid the danger of heavy loss from fire and wind by separating them.
Citation: Hazen, Leslie Eugene. Rural architecture and landscape gardening. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Farm Buildings; Specificiations; Gardening; Kansas; Site Location; Theses